GAMBARAN PENGETAHUAN KELUARGA TENTANG MAKANAN YANG DAPAT MENGENDALIKAN HIPERTENSI - Dwi Wahyuni; Efi Irwansyah Pane (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
The family plays an important role in controlling hypertension through appropriate healthy food choices, including the consumption of fruits and vegetables; hypertension is a serious health problem, often referred to as a silent killer, with a prevalence that continues to increase, yet initial observations indicate that many families still do not fully understand the types of foods that contribute to blood pressure control. This study aims to describe the level of family knowledge regarding foods that can help control hypertension in Neighborhood IV, Selawan Subdistrict, East Kisaran District, Asahan Regency. The study employed a quantitative descriptive method with a survey approach involving families who have members with hypertension, using a research instrument consisting of twelve questions that had undergone validity and reliability testing, while the data were analyzed univariately using frequency distribution. The results showed that the level of family knowledge was in the moderate category, with most respondents able to recognize commonly recommended foods that help lower blood pressure, although understanding of more specific aspects varied. These findings emphasize the need for more targeted health education so that families can implement appropriate dietary patterns to support hypertension control, and the study recommends increasing educational activities focused on improving understanding of healthy foods and strengthening the family’s role in supporting healthy lifestyle behaviors to prevent increases in blood pressure.